Microstructure of PP/clay nanocomposites produced by shear induced injection moulding - Costantino, Alejandra (2012)
The maximum property enhancement in nanoclays reinforced polymers is obtained when high levels of intercalation, exfoliation and dispersion of the nanoclay in the polymer matrix is achieved. Processing of polymer nanocomposites by melt blending techniques requires sufficient stress levels and time for a maximum exfoliation/intercalation of the nanoclays (with minimum polymer degradation), which both are very limited in conventional polymer processing techniques. Shear Controlled Orientation in Injection Moulding, SCORIM, is a non-conventional injection moulding technique based on the concept of in-mould shear manipulation of the melt during the polymer solidification phase. This technique is able of applying high shearing levels to the polymer, leading to high levels of molecular orientation. SCORIM of nanoclay-based polymer nanocomposites may be therefore beneficial for achieving high levels of nanoclay intercalation/exfoliation and orientation, thus imparting improved mechanical properties. In this work, a nanoclay based masterbatch was mixed with polypropylene and direct injection moulded by conventional and SCORIM techniques. In SCORIM, two extreme shear levels were applied by changing processing conditions (melt temperature and shear time). We assess therefore the effect of high shear conditions in the levels of intercalation/exfoliation and orientation of the nanoclay in the polymer matrix and in the mechanical properties of the nanocomposite. The levels of clay intercalation/exfoliation were evaluated by Wide-Angle X-ray Scattering. The microstructure of the moulding was characterized by X-ray diffraction, polarized light microscopy and DSC. Besides influencing the nanoclay morphology, a strong coupling with the polymer morphology is also observed, evidencing the nanoclays as polymer morphology directors.